The philosophy of art education in the context of modern knowledge transformation - Shramko, Oksana (Actual Problems of Mind, 2017)
The author considers the essence and the main goals of the philosophy of art education in the context of postmodernisation and postpostmodernisation of knowledge. It is demonstrated that universal nature of art combining harmonically a logico-rational and imaginative-intuitive self-sentiment makes it especially significant for a general process of reforming of the modern national school.